THE ROLE OF BABUR IN ARCHITECTURE IN INDIA AND THE PRINCIPLES OF THE DEVELOPMENT OF THE ARCHITECTURE OF THE BABURIDS (World Bulletin of Social Sciences, 2021)
In this article, the author has tried to theoretically study and analyze the architecture of the Baburi mosques, which has been controversial among scholars.
Keywords: Babur architecture; Kabuli Garden Mosque; Sambhal Mosque; Ayodhya mosque architecture